PENGARUH PERTUMBUHAN PERUSAHAAN, STRUKTUR MODAL, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN. (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2017) - Yulia Dini Hakiki, 15.05.52.0315; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze the effect of corporate growth, capital structure, profitability and dividend policy on firm value. The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2015-2017 Period. The sample selection uses the purpose sampling method so that the sample is 188 data. The analytical tool used in this study is descriptive analysis and multiple regression analysis. The test results show that the growth of the company has no significant negative effect on firm value. Capital structure has no significant negative effect on firm value. Profitability has a significant positive effect on firm value. And dividend policy has a negative effect that is not significant on firm value.